Quantification of methomyl levels in cabbage, tomato, and soya milk using a renewable amperometric biosensor - Caetano, Josiane; Dragunski, Douglas C.; Pedrosa, Valber A. [UNESP]; Machado, Sergio A.S. (My University, 2013)
An enzymatic biosensor based on inhibition of acetylcholinesterase activity was developed to analyze methomyl contamination in different matrices. The detection limits under optimal working conditions were found to be 30.4 μg L-1 methomyl using the biosensor and 0.15 μg L-1 using HPLC. The biosensor was then applied to analysis of methomyl in fruit and vegetable samples at concentrations in the ppb range in the absence of sample pretreatment. Recovery levels using the biosensor were effective, ranging from 78.0 to 96.5%, while the HPLC method yielded 57.0 to 99.5% recovery. Results for total carbamate concentrations obtained using the acetylcholinesterase biosensor were compared to those obtained using HPLC. © 2013 by ESG.
Keywords: Biosensor; Food analysis; Methomyl; Pesticides